Urolithin A suppresses the proliferation of endometrial cancer cells by mediating estrogen receptor‐α‐dependent gene expression. Issue 11 (25th July 2016) - Zhang, Wei; Chen, Jo‐Hsin; Aguilera‐Barrantes, Irene; Shiau, Chung‐Wai; Sheng, Xiugui; Wang, Li‐Shu; Stoner, Gary D.; Huang, Yi‐Wen
Abstract : Urolithin A (UA) suppresses the proliferation of endometrial cancer cells by mediating estrogen receptor‐α (ERα) dependent gene expression. Black raspberries (BRBs) show chemopreventive effects in animal models and humans. The key components for these effects are not completely understood. Of the 17 BRB constituents and metabolites that we tested, UA inhibited endometrial cancer cell proliferation most effectively. Mechanistically, UA induces the arrest of cell cycle at the G2/M phase and modulates ERα‐dependent gene expression. Abstract : Scope: Obese and overweight women are at high risk of developing endometrial cancer; indeed, many of endometrial cancer patients are obese. The increased number and size of adipocytes due to obesity elevate levels of circulating estrogens that stimulate cell proliferation in the endometrium. However, black raspberries are a promising approach to preventing endometrial cancer. Methods and results: We examined 17 black raspberry constituents and metabolites (10 μM or 10 μg/mL, 48 h) for their ability to prevent endometrial cancer cells from proliferating. Urolithin A (UA) was most able to suppress proliferation in a time‐ and dose‐dependent manner ( p < 0.05). It arrested the G2/M phase of the cell cycle by upregulating cyclin‐B1, cyclin‐E2, p21, phospho‐cdc2, and CDC25B. UA also acted as an estrogen agonist by modulating estrogen receptor‐α (ERα) dependent gene expression in ER‐positive endometrial cancer cells. UA enhanced the expression of ERβ, PGR, pS2, GREB1 while inhibiting the expression of ERα and GRIP1. Coincubating UA‐treated cells with the estrogen antagonist ICI182, 780 abolished UA's estrogenic effects. Knocking down ERα suppressed PGR, pS2, and GREB gene expression but increased GRIP1 expression. Thus, UA's actions appear to be mediated through ERα. Conclusion: This study suggests that UA modulates ERα‐dependent gene expression, thereby inhibiting endometrial cancer proliferation.